A randomized controlled trial on the effectiveness of a portable patient education video prior to coronary angiography and angioplasty. Issue 7 (22nd December 2019) - Yap, Jonathan; Teo, Tse Y.; Foong, Priscilla; Binte Hussin, Norwati; Wang, Hannah; Shen, Tong; Yeo, Khung K.
Abstract: Introduction: Time limitations in busy clinical settings may impede adequate explanation of coronary angiography/angioplasty. We aim to evaluate the effectiveness of a portable patient education video in improving knowledge and allaying patient's anxiety. Methods: Consecutive patients undergoing coronary angiography/angioplasty were prospectively recruited over 1 year from a tertiary cardiac institution. A 3‐min animated patient education video on the procedure was developed to be shown on a tablet. Patients were randomized 3:1 into an intervention group (video plus routine care) versus a control group (routine care). Before the procedure, a self‐administered questionnaire was conducted in both groups. The questionnaire was repeated post‐video in the intervention group. Results: A total of 332 patients (252 intervention groups, 80 controls) were recruited. At baseline, the intervention group had lower knowledge scores ( p = .022) and similar anxiety scores ( p = .323) compared with the control group. After the video, the intervention group had significantly higher knowledge scores ( p ≤ .001) and lower anxiety scores ( p ≤ .001). Within the intervention group, there was a significant increase in knowledge scores ( p ≤ .001) and reduction in anxiety scores ( p ≤ .001) before versus after watching the video. In the subset of patients who had previously undergone a similar procedure ( n = 131), there was also significant improvement in knowledge scores and reduction in anxiety scores ( p < .001). The video is accessible at https://youtu.be/R8AdaIbNq7Y . Conclusion: The video improved knowledge and reduced anxiety in patients undergoing coronary angiography and angioplasty. This is a useful adjunct to incorporate into existing workflows to improve patient care.